Analysis of Factors Related to Work Productivity in Workers in the Nutrition and Special Food Division - Harahap, Ramayani Anwar; Suraya, Rani; Harahap, Reni Agustina (Indonesian Journal of Global Health Research, 2024)
The problem of productivity in an organization is an important study, especially in relation to human resources as one of the inputs to productivity. Therefore, the productivity of human resources (employees) is absolutely considered. To achieve maximum work productivity, organizations must ensure the selection of the right people with the right jobs and conditions that allow them to work optimally. The purpose of this study was to determine the factors related to work productivity in workers. This study used quantitative methods with a cross sectional design. The sampling technique is Total Sampling. The population and sample in this study were all 40 workers in the Nutrition and Special Food Division. Data collection using questionnaires and variables studied include Nutritional Status, Work Motivation, and Workload. The results of this study show that there is a relationship between Nutritional Status and Work Productivity (p value = 0.025), there is a relationship between Work Motivation and Work Productivity (p value = 0.024), and there is a relationship between Workload and Work Productivity (p value = 0.013). The results of research on factors related to low work productivity, nutritional status, low work motivation and risky workload that can cause losses to the company.